The pivotal role of nursing personnel in burn care - Greenfield Elisabeth (Indian Journal of Plastic Surgery)
The nurses play an important role in the overall management of a burn patient. They must be well versed with the various protocols available that can be used to rationally manage a given situation. The management not only involves medical care but also a psychological assessment of the victim and the family. The process uses a scientific method to combine systems theory with the art of nursing, entailing both problem solving techniques and a decision making process. It involves assessment of the patient to arrive at a diagnosis and then determining the patient goals .An action plan is implemented and is evaluated in the context of patient response . The article discusses many such scenarios in burn patients and outlines the nursing care plans.